2004
DOI: 10.1108/13620430410544364
|View full text |Cite
|
Sign up to set email alerts
|

A study of career needs, career development programs, job satisfaction and the turnover intentions of R&D personnel

Abstract: This study set to explore the career needs and proposes the concept of the gap between career development programs and career needs, and its subsequent effect on job satisfaction, turnover intention, in an effort to contribute to the field of career management, through the effective integration of career needs and career development programs. Questionnaires were completed by 367 R&D personnel from Hsinchu Science-based Industrial Park (HSIP) in the north of Taiwan. The results reveal that R&D personnel have ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 28 publications
12
127
0
2
Order By: Relevance
“…If the nature of the deficiencies is only slight, job satisfaction and morale are reduced. If it is more serious, affective commitment will decrease, and turnover intentions will increase, impacting upon corporate growth and long-term performance (Chen, Chang & Yeh, 2004). We advocate that, next to a sincere involvement of supervisors with the well-being and work-home interference of their staff in health care settings, there is a serious need for more social support networks aimed at increasing collegial support as well.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…If the nature of the deficiencies is only slight, job satisfaction and morale are reduced. If it is more serious, affective commitment will decrease, and turnover intentions will increase, impacting upon corporate growth and long-term performance (Chen, Chang & Yeh, 2004). We advocate that, next to a sincere involvement of supervisors with the well-being and work-home interference of their staff in health care settings, there is a serious need for more social support networks aimed at increasing collegial support as well.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Training offered to employees, may help them reduce their anxiety or frustration, brought on by work demands, that they are not familiar with, and they are lacking the skills to handle effectively (Chen et al, 2004). Although there has been no direct link in the literature between training and job satisfaction, Rowden (2002) and Rowden and Conine (2005), propose that training may be used as a tool to increase job satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, many researches revealed that motivation has an absolute link with job satisfaction and employee commitment in an organization. (Basset-Jones and Lloyd, 2005;Chen et al, 2004;Lok and Crawford, 2004). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Although our knowledge on emotion work is still limited, potential human resource practices can include: the provision of information to frontline employees on the nature of emotion work; mentoring by senior colleagues or more experienced peers (e.g., Eby, 1997;King, Xia, Campbell-Quick & Sethi, 2005;van Emmerik, 2004); and the design of frontline service work in a way that reduces the demands on intensity, variety and frequency of emotional display (taking into account that our results suggest that these are the demands that are mostly related to negative outcomes rather than the sheer fact that employees are required to act in their Emotion Work and Work Attitudes in Hellas 33 encounters with customers). Such specific-to-emotion-work human resource systems could be supplemented by practices that are traditionally utilized as means against negative work attitudes and voluntary turnover, for example, fairly designed and managed reward systems, and opportunities for development (e.g., Chen, Chang & Yeh, 2004). …”
Section: Emotion Work and Work Attitudes In Hellas 31mentioning
confidence: 99%